2015
DOI: 10.3340/jkns.2015.57.3.221
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hemifacial Spasm Caused by an Artery Passing Through the Facial Nerve

Abstract: Hemifacial spasm (HFS) is a clinical syndrome characterized by unilateral facial nerve dysfunction. The usual cause involves vascular compression of the seventh cranial nerve, but compression by an artery passing through the facial nerve is very unusual. A 20-year-old man presented with left facial spasm that had persisted for 4 years. Compression of the left facial nerve root exit zone by the anterior inferior cerebellar artery (AICA) was revealed on magnetic resonance angiography. During microvascular decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Oh et al reported a left HFS presenting in a 20-year-old male patient. The penetrating offender in this patient was the AICA; after decompression, the spasm disappeared, but definite facial palsy occurred [15]. From this case report and from our study, it is apparent that HFS caused by the penetrating type occurs at a relatively young age compared to the general population.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Oh et al reported a left HFS presenting in a 20-year-old male patient. The penetrating offender in this patient was the AICA; after decompression, the spasm disappeared, but definite facial palsy occurred [15]. From this case report and from our study, it is apparent that HFS caused by the penetrating type occurs at a relatively young age compared to the general population.…”
Section: Discussionmentioning
confidence: 51%
“…The facioauditory primordium, the origin of the facial nerve, appears in the third week of gestation. It then splits into two sections at the end of the fourth week and is complete by the fifth or sixth week of gestation [15,23]. The AICA begins to develop later, in the gestational fourth or fifth month, when the facial nerve is already fairly well-developed [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases of trigeminal neuralgia, intraneural vessels penetrating the trigeminal nerve have been identified [ 11 , 12 ]. Hemifacial spasm patients whose symptoms were caused by intraneural vessels passing through the facial nerve were also reported [ 13 , 14 ]. Considering the abovementioned cases in which the intraneural vessels resulted in neuropathies, penetration of the posterior division of the femoral nerve by the arterial branch might also have caused pain or paresthesia, particularly of the medial aspect of the leg in the distribution of the saphenous nerve derived from the posterior division.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Oh et al ., it was hypothesized that AICA passes through the facial nerve during developmental stages. [ 4 ] Since this abnormality is not life-threatening, all treatment options, including expectant management, surgery with microvascular decompression, botulinum toxin injection, among other various medications, need to be carefully considered. Microvascular decompression is the permanent treatment option but carries many risks involved with any surgical procedure.…”
Section: Discussionmentioning
confidence: 99%